1993
DOI: 10.1002/ajmg.1320450109
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of craniofacial anomalies in utero: Fetal Alcohol and Crouzon Syndromes and Thanatophoric Dysplasia

Abstract: The study of fetal growth and development by ultrasound has been greatly facilitated in the past few years by the availability of anthropometric standards for the fetal body. Thus, the obstetrician is able to discern between normal and grossly abnormal, and even to quantitate certain fine fetal structures such as the face. This paper presents results obtained from a group of 5 patients referred to the Medical Center from private practices in Indianapolis, Indiana. Prenatal cephalometric analyses by ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Escobar et al employed Z ‐scores of 22 craniofacial measurements by 2D ultrasound to describe pattern profile variability in fetal alcohol syndrome, Crouzon syndrome and thanatophoric dysplasia. Although not all fetuses with fetal alcohol syndrome had a variability index in the abnormal range, mid‐face measurements in these fetuses were very similar and gave a pattern distinctive for this syndrome4.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Escobar et al employed Z ‐scores of 22 craniofacial measurements by 2D ultrasound to describe pattern profile variability in fetal alcohol syndrome, Crouzon syndrome and thanatophoric dysplasia. Although not all fetuses with fetal alcohol syndrome had a variability index in the abnormal range, mid‐face measurements in these fetuses were very similar and gave a pattern distinctive for this syndrome4.…”
Section: Discussionmentioning
confidence: 89%
“…Escobar et al employed this method for ultrasound‐derived cephalometric measurements2, 3. The authors found that pattern profile analysis may have an additional value in the diagnosis of fetuses with mild abnormalities or abnormality patterns4.…”
Section: Introductionmentioning
confidence: 99%
“…This method was applied by Escobar et al , using 2D ultrasound in fetal alcohol syndrome, Crouzon syndrome and thanatophoric dysplasia. They stressed the potential value of this method for documenting craniofacial dysmorphology in utero 20.…”
Section: Discussionmentioning
confidence: 99%
“…There are many landmarks and planes from which to choose, and normative data have been established [Riolo et al, 1974;Saksena et al, 1987]. This technique has been applied to syndrome diagnosis, to the evaluation of developmental abnormalities [Pruzansky, 1977;Cohen, 1981Cohen, , 1985Kreiborg, 1985], and to the quantitation of craniofacial anomalies in utero [Escobar et al, 1993]. Richtsmeier [1987,1988] has taken cephalometrics a stage further using finite element scaling analysis, which quantifies the difference in size and shape between forms, without reference to any fixed arbitrary registration point or orientation line.…”
Section: Cephalometrymentioning
confidence: 99%